2020
DOI: 10.1063/5.0013534
|View full text |Cite
|
Sign up to set email alerts
|

Stability and transition on a Coandă cylinder

Abstract: An experimental stability and transition investigation of a centrifugally unstable wall jet blown from a slot over a circular Coandă cylinder was conducted using flow visualization and particle image velocimetry. Clear and unambiguous observations of spontaneously generated stationary streamwise structures, never observed previously, were analyzed using standard image processing techniques. These structures ultimately exhibited a secondary time-dependent wavy instability that was followed by transition to turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
0
5
0
6
Order By: Relevance
“…Different from the well-studied planar mixing layer, there are not only the Kelvin–Helmholtz type inflectional instability (Neuendorf & Wygnanski 1999; Watanabe & Nagata 2021), but also the Taylor–Görtler type of centrifugal instability (Görtler 1941; Cunff & Zebib 1996; Matsson & John 1998) in the curved jet shear layer. A series of previous studies have shown that this additional centrifugal instability plays an important role in the development of a convex wall jet (Fujisawa & Kobayashi 1987; Neuendorf & Wygnanski 1999; Likhachev, Neuendorf & Wygnanski 2001; Neuendorf, Lourenco & Wygnanski 2004; Han, De Zhou & Wygnanski 2006; Dunaevich & Greenblatt 2020; Pandey & Gregory 2020, 2021). Fujisawa & Kobayashi (1987), Neuendorf & Wygnanski (1999) and Likhachev et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the well-studied planar mixing layer, there are not only the Kelvin–Helmholtz type inflectional instability (Neuendorf & Wygnanski 1999; Watanabe & Nagata 2021), but also the Taylor–Görtler type of centrifugal instability (Görtler 1941; Cunff & Zebib 1996; Matsson & John 1998) in the curved jet shear layer. A series of previous studies have shown that this additional centrifugal instability plays an important role in the development of a convex wall jet (Fujisawa & Kobayashi 1987; Neuendorf & Wygnanski 1999; Likhachev, Neuendorf & Wygnanski 2001; Neuendorf, Lourenco & Wygnanski 2004; Han, De Zhou & Wygnanski 2006; Dunaevich & Greenblatt 2020; Pandey & Gregory 2020, 2021). Fujisawa & Kobayashi (1987), Neuendorf & Wygnanski (1999) and Likhachev et al.…”
Section: Introductionmentioning
confidence: 99%
“…The streamwise vortices induced by the centrifugal effect are considered to be responsible for the mixing enhancement in the curved jet. Dunaevich & Greenblatt (2020) firstly observed the spontaneously generated stationary streamwise structures using flow visualization and particle image velocimetry. These structures ultimately exhibited a secondary time-dependent wavy instability.…”
Section: Introductionmentioning
confidence: 99%
“…They include control of circulation in aeronautics (Englar, Smith, Kelley, & Rover, 1994a, 1994b; Nishino, Hahn, & Shariff, 2010; Semaan et al., 2016), wind energy (Djojodihardjo et al., 2013) and drag reduction of bluff bodies (Barros, Borée, Noack, Spohn, & Ruiz, 2016; Geropp & Odenthal, 2000; Haffner, Borée, Spohn, & Castelain, 2020). The flow physics of such jets, on a convex surface, has been extensively investigated in the literature (Dunaevich & Greenblatt, 2020; Gross & Fasel, 2006; Neuendorf, Lourenco, & Wygnanski, 2004; Neuendorf & Wygnanski, 1999) and explained as the result of streamwise Görtler-like vortices. It has to be noted that, for most of the above applications and analyses, the flow is propagating on a convex surface, and the jet has a span width that is several orders of magnitude greater than the jet nozzle length in the streamwise direction.…”
Section: Introductionmentioning
confidence: 99%
“…Han, Zhou & Wygnanski (2006) used spanwise heterogeneities at the nozzle lip of a cylinder apparatus to force streamwise vortices, and found that these vortices were subsequently sustained by the centrifugal effects. In the latest work of Dunaevich & Greenblatt (2020), the spontaneously generated stationary streamwise structures were first observed using flow visualization and particle image velocimetry. These structures ultimately exhibited a secondary time-dependent wavy instability.…”
Section: Introductionmentioning
confidence: 99%